Factors Influencing Academic Writing Behaviour Among Undergraduates - Mohamad, Faizah; Anuar, Nadia; Shidrah Mat Daud, Nor (International Journal of English Language Education, 2022)
Writing is a crucial skill for university students to succeed in the current content-driven era. However, many students are reported to be intimidated by writing as they find the task daunting, thus affecting their participation in writing activities. Students also rarely show encouraging writing behaviour, which leads to unsatisfactory written work. This study aimed to examine factors that contribute to their writing behaviour. A quantitative research method by means of a survey design was employed for data collection. A 43-item questionnaire was distributed randomly using a Google Form link to 84 undergraduate students who were undertaking various fields of study at a public university. Section A of the questionnaire queries the students’ demographic profile, whereas Section B, C, and D seek responses on their psychological state, confidence, and attitudes, respectively. Section E queries their writing behaviour. Descriptive analysis was performed on each factor, and Pearson’s correlation was used to analyse the relationship between the factors and the students’ writing behaviour. Finally, a stepwise multiple regression was employed to discover the factor most contributing to the students’ writing behaviour. The findings indicate that confidence and attitude factors have a significant relationship with the students’ writing behaviour, but the relationship between psychological state factors and writing behaviour was not significant. This finding enhances the understanding of the essentiality of attitude in facilitating students’ writing mastery.